Mutual Promotion of Reading and Expression: Research into Children’s Picture Book Teaching of I Wanna Iguana - Jing Xiang; Ying Yan (International Dialogues on Education: Past and Present, 2020)
The narrative function of children’s picture books connects the exquisite, meaningful and colorful paintings with easy and imaginative words. A teaching process, which is called the circulation process, happens when teachers and children are reading the pictures and words repeatedly. This process involves four stages: lead-in, telling the story, retelling the story and utilizing the retold story. Teacher may understand children’s knowledge, cognitive features as well as nature of picture books and paintings effectively. Then the vivid illustration of story line encourages children to think from others’ views and communicate with different people in the world. In such a way, we aim to establish a brand new teaching culture consisted of national memory and traditional Chinese culture elements.